Formation of an Optimal Portfolio of Shares of LQ-45 Indexed Companies Using the Markowitz Index Model - Yoseph Ferdinand (CONTABILITA : Journal of Accounting and Finance, 2026)
Investment is an activity that cannot be separated from the business world.To achieve the expected return and reduce risk, it is necessary for a company to diversify its business. Diversification means investors need to form a portfolio through the selection of a combination of assets in such a way that risk can be minimized without reducing the expected return, because reducing risk without reducing return is the investor's goal in investing.The research Data used is historical data on the closing price of the company's shares indexed LQ-45 published by the Indonesia Stock Exchange. Data obtained from the official website of the Indonesia Stock Exchange, namely www.idx.co.id and www.yahoofinance.co.id in the form of quantitative data. The Markowitz model is a portfolio determination model that emphasizes the relationship between Return and investment risk